Improving Students’ Speaking Skill By Retelling Technique Using Video (An Experimental Study at the Second Grade Students of MTsN Kuta Baro Aceh Besar) - Syahra Fitri; Endang Komariah; Hendra Heriansyah (Universitas Syiah Kuala, 2017)
This study aims at examining whether or not the use of retelling technique using video can improve students’ performance in English speaking. The researcher focuses on the application of retelling technique using video in teaching speaking. The type of text that is taught is narrative text in the form of simple monologue. The study was conducted in Islamic Junior High School (MTsN) Kuta Baro Aceh Besar. Quantitative approach with pre-experimental type of one group pre-test post-test design was used. The data was obtained by giving a set of tests in the form of oral test. The students were asked to retell the story that they had watched. Data were analyzed by using speaking criteria proposed by Brown (2004). In addition, statistical analysis used to analyze the data. From the results of the study, it reveals the average score of the students on the pretest is 26.8, while on the posttest is 55.2. Moreover, the researcher found that the t-score in this research is higher than the score of t-table (ts = 4.856 tt = 2.080). It shows that there is a significant improvement on students’ speaking skill after the implementation of retelling technique using video. It means that retelling technique using video can be one of the alternative techniques used by the teacher in teaching speaking.